Impacts of the properties heterogeneity on 3D magnetic dusty nanofluids flow in porous enclosures with cylinders - Z. Z. Rashed (Scientific Reports, 2022)
Abstract This paper examines the controlling of the three dimensional dusty nanofluid flow using the two circular cylinders having different thermal conditions. The cylinders are located in the middle area while the location of the right cylinder is changeable. The 3D (three dimensional) cubic flow domain is filled by a non-Darcy porous medium and a magnetic field in Z-direction is taken place. The non-homogeneous two phase model of the nanofluid is applied while the permeability and thermal conductivity of the porous medium are assumed heterogonous. The current situation is represented by two systems of the equations for the nanofluid and dusty phases. The solutions methodology is depending on the 3D SIMPLE scheme together with the finite volume method. Here, It is focused on the distance between the cylinders $$δ\, (0.3\le δ \le 0.6)$$ δ ( 0.3 ≤ δ ≤ 0.6 ) , the Darcy number $$Da\, ({10}^{-2}\le Da\le {10}^{-5})$$ D a ( 10 - 2 ≤ D a ≤ 10 - 5 ) , the dusty parameter $${α }_{d}\,(0.001\le {α }_{d}\le 0.1)$$ α d ( 0.001 ≤ α d ≤ 0.1 ) , the average nano-parameter $${φ }_{av}\,(0.01\le {φ }_{av}\le 0.03)$$ ϕ av ( 0.01 ≤ ϕ av ≤ 0.03 ) . The major outcomes indicating to that the flow can be well controlled using the inner isothermal cylinders. Also, the cases of the heterogeneity in $$X{-}Y$$ X - Y and $$X{-}Z$$ X - Z directions give the lowest values of $${Nu}_{av}$$ Nu av . Both the flow and heat transfer rate are enhanced as $$δ $$ δ is increased.